Millipede Composting: A Novel Method for Organic Waste Recycling - P. Alagesan2, M. Karthigeyan1* and (Recent Research in Science and Technology, 2011)
Millipedes are known to be macro detrivorous terrestrial arthropods which feed on decaying vegetable matter and mineral soils. An attempt was made to assess the ability of millipede Xenobolus carnifex in composting the commonly available organic wastes such as leaf litter, sugarcane trash, rice husk and sawdust and the influence of millicompost prepared from different organic wastes on the growth of vegetable plant, Abelmoschus esculentus. In addition, biochemical constituents were also estimated in the millicompost by using standard procedures. The millipede compost derived from leaf litter residues possessed better nutritional content than other organic residues. Further plant height, leaf number, leaf length and fruit length and weight were enhanced when leaf litter derived millicompost was applied. Compost derived from different organic wastes could act as effective organic manure to the crop plants and ecofriendly alternative source to minimize the usage of synthetic fertilizers.